Pain and Interventions in Stage IV Non-Small Cell Lung Cancer: A Province-Wide Analysis - Vivian S. Tan; Michael C. Tjong; Wing C. Chan; Michael Yan; Victoria Delibasic; Gail Darling; Laura E. Davis; Mark Doherty; Julie Hallet; Biniam Kidane; Alyson Mahar; Nicole Mittmann; et al. (Current Oncology, 2023)
Pain is a common symptom in stage IV non-small cell lung cancer (NSCLC). The objective of the study was to examine the use of interventions and factors associated with interventions for pain. A population-based cohort study in Ontario, Canada was conducted with patients diagnosed with stage IV NSCLC from January 2007 to September 2018. An Edmonton Symptom Assessment System (ESAS) score of ≥4 defined moderate-to-severe pain following diagnosis. The study cohort included 13,159 patients, of which 68.5% reported at least one moderate-to-severe pain score. Most patients were assessed by a palliative care team (85.4%), and the majority received radiation therapy (73.2%). The use of nerve block was rare (0.8%). For patients ≥65 years of age who had drug coverage, 59.6% received an opiate prescription. Patients with moderate-to-severe pain were more likely to receive palliative assessment or radiation therapy compared to patients with none or mild pain. Patients aged ≥70 years and with a greater comorbidity burden were associated with less likelihood to receive radiation therapy. Patients from rural/non-major urban residence and with a greater comorbidity burden were also less likely to receive palliative care assessment. Factors associated with interventions for pain are described to inform future symptom management in this population.